Effect of Furfural Residue Ash (FRA) as Additive on Portland Cement and Magnesium Oxysulfate Cement - Yining Sun; Ruize Sun; Xin Jia; Ping An; Yujian Liu; Jinjie Wu; Xingfei Song; Guangwen Xu (BioResources)
The global production of furfural generates substantial amounts of furfural residue waste annually, which, if not properly managed, can lead to significant environmental pollution. However, the ash produced from the combustion of this biomass waste shows promise as a cement additive, offering an innovative solution for furfural residue management. In this study, ash obtained from the combustion of furfural residue in industrial boilers was used as an additive in both Portland cement and magnesium oxysulfate cement, with concentrations ranging from 5% to 20%. Mortar specimens were then prepared and tested for compressive and flexural strength at 3, 7, and 28 days. The results indicated that at a 10 wt% addition, the formation of cotton-like structures and ettringite needles was most pronounced, resulting in the highest compressive and flexural strengths in the Portland cement specimens. Similarly, in magnesium oxysulfate cement, a 10 wt% ash addition significantly promoted the formation of the 5·1·7 phase, leading to the highest compressive strength. In summary, under appropriate conditions, furfural residue ash can be effectively utilized as a cement additive, contributing to resource recovery and sustainable waste management.